An Examination of the Leadership and Management Traits and Style in the Forest Fire Incident Command System: The Cyprus Forest Fire Service - Nicolas-George Homer Eliades; Achilleas Karayiannis; Georgios Tsantopoulos; Spyros Galatsidas (Fire)
Since the early 21st century, wildlands have witnessed an effusion of wildfires, with climate and social changes resulting in unanticipated wildfire activity and impact. For forest fires to be prevented and suppressed effectively, forest firefighting forces have adopted a specific administrative system for organizing and managing the fighting force. Under the administrative system, a debate on desired “leadership and management qualities” arises, and hence, this study sought to identify the leadership and management traits that should distinguish individuals in the forest fire incident command system (FFICS) applied by the Department of Forests (Cyprus). The research subject was addressed using mixed method research, employing quantitative and qualitative data. Both datasets were used to distinguish the purposes of the applied triangulation, enabling the examination of differentiation between the trends/positions recorded in terms of the object of study. These findings point to ideal forms of transformational leadership and neoclassical management. The outcomes suggest that at the individual level, the leaders of each of the operating structures should develop leadership qualities related to emotional intelligence, empathy, judgment, critical thinking, and especially self-awareness of strengths and weaknesses. At the stage of pre-suppression, a democratic leadership style (or guiding style) is supported, while during the operational progress stage of the FFICS, a “hybrid” leadership style is suggested, borrowing elements from the democratic and authoritarian (or managerial) leadership styles. The administrative skills of FFICS leaders should include the moral and psychological rewards of subordinates, job satisfaction and recognition, and two-way communication. The current study illustrates the need for divergent leadership and management traits and styles among the different hierarchical structures of the FFICS.